PPC-based high-tensile-strength TPU material and preparation thereof
By introducing specific epoxy compounds and catalysts into PPC-based TPU materials and preparing PPC-based high tensile strength TPU materials using the twin-screw reaction extrusion mechanism, the problem of insufficient tensile strength of existing TPU materials is solved, and the high tensile strength and simple preparation process of the material are achieved.
Patent Information
- Application Number
- CN202510595878.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-05
AI Technical Summary
The tensile strength of existing PPC-based TPU materials is not high and cannot meet the product application requirements of high tensile strength requirements.
Using a combination of polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, and specific epoxy compounds and catalysts, a PPC-based high tensile strength TPU material is prepared through a twin-screw reaction extrusion mechanism, and the cross-linking effect of epoxy compounds is used to improve the mechanical properties of the material.
It significantly improves the tensile strength of TPU materials, has a simple preparation process, and is suitable for industrial promotion.
Smart Images

Figure CN120424299A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a thermoplastic elastomer material, in particular to a PPC-based high-tensile-strength TPU material and its preparation method. Background Art
[0002] TPU, or thermoplastic polyurethane, is a polymer material between rubber and plastic, with unique physical and chemical properties. It is widely used in waterproof films, shoe materials, automotive parts, and wear-resistant accessories for smart wearable devices.
[0003] PPC, a polypropylene carbonate material, boasts advantages such as biodegradability, non-toxicity, and environmental friendliness, and has a wide range of applications in the field of polymer materials. For example, Wu et al., in their comparative analysis of the performance of thermoplastic polyurethane and biodegradable polyurethane-polypropylene carbonate, noted that combining TPU with PPC to create a TPU-PPC composite material exhibits improved physical and mechanical properties, water resistance, chemical stability, and biodegradability. However, the TPU-PPC composite material described in this article is prepared by blending PPC with a finished TPU product, rather than directly using PPC as the raw material to prepare the TPU material.
[0004] The patent with publication number CN102838717A discloses a process for preparing thermoplastic polyurethane elastomer using polypropylene carbonate as a soft segment. Specifically, a diisocyanate and a catalyst are first added to polypropylene carbonate polyol to react, a chain extender is added after the reaction to carry out a chain extension reaction, and the thermoplastic polyurethane elastomer is obtained by drying and curing. The process of the present invention is simple, the raw material source is abundant, the production cost is low, and the thermoplastic polyurethane elastomer is prepared by a prepolymerization method. The resulting product does not turn yellow, has strong plasticity and excellent performance, and the elastomer tensile properties can be adjusted at will. The main feature of the material disclosed in this patent is that although it has very good plasticity and elongation at break, its tensile strength is not high and cannot meet the industry application requirements of products with high tensile strength requirements.
[0005] Epoxy compounds such as Epoxidized soybean oil and BASF 4468 are often used as plasticizers and chain extenders in polymer materials. In addition, there are reports that Epoxidized soybean oil can be used as a hydrolysis resistance modifier for TPU. For example, patent publication number CN117229746A discloses a TPU hot melt adhesive film and a preparation method thereof. The film includes the following components in parts by weight: 100 parts of polyester TPU particles, 5 to 30 parts of Epoxidized soybean oil, 5 to 30 parts of modified thermoplastic elastomer, 0.1 to 5 parts of imidazole accelerator and 0.5 to 3 parts of antioxidant; the modified thermoplastic elastomer is a 1,2-syndiotactic polybutadiene polymer modified by a high-flow polyester TPU blend, and the high-flow polyester TPU has a melt index of ≥20 g / 10 min under test conditions of 190°C and 2.16 kg. In the hot melt adhesive film of the present invention, the hydrolysis resistance and mechanical properties of the TPU hot melt adhesive film are improved through the simultaneous action of multiple components.
[0006] In their study "Study on Hydrolysis Resistance and Aging of Thermoplastic Polyurethane Elastomers," Liu et al. analyzed the effects of three epoxy compounds—PGE, KH560, and E51—on the mechanical properties of TPU materials. They modified the TPU material by adding PGE, KH560, and E51 to it through physical blending. Test results showed that while the addition of some epoxy compounds improved the mechanical properties and tensile strength of the TPU to a certain extent, the improvement was very limited, and even a slight increase in the added amount resulted in a decrease in tensile strength. Therefore, the technical solution in this document cannot effectively improve the mechanical properties of TPU materials using epoxy compounds, nor can it effectively increase the tensile strength of PPC-TPU.
[0007] In summary, although PPC-based TPU materials have been publicly reported, and the use of chain extenders such as epoxidized soybean oil and BASF 4468 in TPU materials is also a conventional choice, the use of epoxy compounds such as epoxidized soybean oil and BASF 4468 in PPC-based TPU materials as one of the polymerization reaction raw materials, mainly to provide cross-linking, thereby improving the mechanical properties of TPU materials and increasing their tensile strength, has not been reported yet. Summary of the Invention
[0008] In order to solve the above technical problems, the present invention provides a PPC-based high tensile strength TPU material and its preparation method. The TPU material of the present invention has the characteristics of high tensile strength, simple preparation process and can be industrialized and promoted.
[0009] One of the technical solutions of the present invention:
[0010] Provided is a PPC-based high-tensile-strength TPU material composed of polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, an epoxy compound, and a catalyst.
[0011] Preferably, in the aforementioned PPC-based high tensile strength TPU material, the mixing mass ratio of the polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst is 100:13.07-18:48.89-63:0.81-0.9:0.26-0.33.
[0012] Preferably, in the aforementioned PPC-based high tensile strength TPU material, the mixing mass ratio of the polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst is 100:14-16:52-58:0.85-0.88:0.29-0.31.
[0013] Preferably, in the aforementioned PPC-based high tensile strength TPU material, the mixing mass ratio of the polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst is 100:15:55:0.86:0.3.
[0014] Preferably, in the aforementioned PPC-based high tensile strength TPU material, the epoxy compound is one of epoxidized soybean oil, ADR4468, ADR4368, ADR4380, ADR4385, ADR4400, KL-E4300, KL-E4370, KL-E4370B, X-U993, SAG-008 or BTCE-9019.
[0015] Preferably, in the aforementioned PPC-based high tensile strength TPU material, the catalyst is a tertiary amine catalyst, or a mixture of a tertiary amine catalyst and an organotin catalyst.
[0016] Preferably, in the aforementioned PPC-based high tensile strength TPU material, the tertiary amine catalyst is triethylenediamine or N,N-dimethylcyclohexylamine; and the organic tin catalyst is one of stannous octoate, dibutyltin dilaurate or dibutyloctyltin dilaurate.
[0017] In this solution, the addition of epoxy compounds and the selection of catalysts are key factors. The selected catalyst can not only catalyze the epoxy ring-opening, but also catalyze the reaction between polypropylene carbonate, 1,4-butanediol and diphenylmethane diisocyanate. If the catalyst is omitted, the degree of the entire polymerization reaction will be very low, and the product will be soft and sticky, with no strength and no practicality. If other conventional polyurethane catalysts are selected, they will have no catalytic effect on epoxy compounds, and epoxy compounds will rarely participate in the reaction, failing to achieve the actual improvement effect of adding epoxy compounds on the material in this application.
[0018] The second technical solution of the present invention:
[0019] Provided is a method for preparing the aforementioned PPC-based high tensile strength TPU material, which comprises mixing the components and then extruding the mixture using a twin-screw reaction extruder.
[0020] Preferably, in the aforementioned method for preparing a PPC-based high tensile strength TPU material, the temperature of the twin-screw reaction extruder is 140-200°C.
[0021] Preferably, in the aforementioned method for preparing a PPC-based high tensile strength TPU material, the temperature of the twin-screw reaction extruder is 160-180°C.
[0022] Preferably, in the aforementioned method for preparing a PPC-based high tensile strength TPU material, the TPU material extruded by the twin-screw reaction extruder is further aged at 70-90° C. for 20-30 hours.
[0023] Preferably, in the aforementioned method for preparing a PPC-based high tensile strength TPU material, the aging temperature is 80° C. and the aging time is 24 hours.
[0024] Beneficial effects of the present invention:
[0025] 1. The present invention selects a suitable catalyst and type of epoxy compound, so that the epoxy compound can open the ring and react with polypropylene carbonate, 1,4-butanediol and diphenylmethane diisocyanate, thereby increasing the crosslinking degree between the components, thereby effectively improving the mechanical properties of the TPU material and making it have higher tensile strength.
[0026] 2. The PPC raw material of the present invention can not only react with the epoxy compound under the action of the catalyst, but also generate a new hydroxyl group after the hydroxyl group reacts with the epoxy. Therefore, the addition of the epoxy compound will not affect the hydroxyl content in the raw material, which can ensure the normal progress of the subsequent reaction.
[0027] 3. The preparation process of the TPU material of the present invention is simple and suitable for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Attachment Figure 1 Thermogravimetric analysis diagrams of the TPU materials prepared in Comparative Example and Example 1;
[0029] from Figure 1 It can be seen that the thermal stability of TPU materials is relatively high, and the temperature for losing 5% of the mass reaches 300°C; however, the amount of residual carbon at 400°C is higher when ADR-4468 is added, indicating that the added ADR-4468 does play a cross-linking role.
[0030] Attachment Figure 2 This is the GPC test result of the TPU material prepared in the comparative example;
[0031] Attachment Figure 3 This is the GPC test result of the TPU material prepared in Example 1;
[0032] from Figure 2 and Figure 3 The comparison shows that Figure 2 The number average molecular weight (Mn) of the TPU product without ADR-4468 is 59649, the weight average molecular weight (Mw) is 164647, and the polydispersity coefficient (PD) is 2.76. Figure 3 The TPU product containing ADR-4468 exhibited an Mn of 73043, an Mw of 250809, and a PD of 3.43. GPC results showed a significant increase in molecular weight after the addition of ADR-4468, providing molecular-level evidence for the strength improvement and demonstrating that ADR-4468 indeed plays a role in cross-linking and strengthening. DETAILED DESCRIPTION
[0033] The present invention will be further described below with reference to the examples, but they are not intended to limit the present invention.
[0034] Embodiments of the Invention
[0035] The specific parameters of the epoxy compound used in the embodiment of the present invention are as follows:
[0036] Comparative Example 1 of the present invention
[0037] A PPC-based TPU material without epoxy compound added is composed, by weight, of 100 parts of polypropylene carbonate, 13.07 parts of 1,4-butanediol, 48.89 parts of diphenylmethane diisocyanate, and 0.26 parts of triethylenediamine; the preparation method thereof is as follows:
[0038] The raw materials in the aforementioned parts by weight were mixed and added to a twin-screw reaction extruder at an extrusion temperature of 180° C. The extruded material was aged at 80° C. for 24 hours to obtain a PPC-based TPU material without adding epoxy compounds.
[0039] Comparative Example 2 of the present invention
[0040] In the molecular chains produced by the polymerization reaction of the TPU of this invention, the segments formed by the reaction of a higher molecular weight diol with MDI are flexible and are generally referred to as "soft segments," while the segments formed by the reaction of a lower molecular weight diol with MDI are rigid and are generally referred to as "hard segments." A high proportion of soft segments results in a soft and tough polymer, while a high proportion of hard segments results in a hard and brittle polymer. Furthermore, the crosslinking effect of the epoxy compound also significantly affects hardness and elongation at break.
[0041] A PPC-based TPU material is composed, by weight, of 100 parts of polypropylene carbonate, 9 parts of 1,4-butanediol, 37.54 parts of diphenylmethane diisocyanate, 0.73 parts of ADR4468, and 0.21 parts of triethylenediamine; the preparation method is as follows:
[0042] The raw materials in the aforementioned parts by weight were mixed and added to a twin-screw reaction extruder at an extrusion temperature of 160° C. The extruded material was aged at 75° C. for 28 hours to obtain a PPC-based high tensile strength TPU material having a molar ratio of soft segment to hard segment of 1:2.
[0043] Comparative Example 3 of the present invention
[0044] A PPC-based high-tensile strength TPU material is composed, by weight, of 100 parts of polypropylene carbonate, 22 parts of 1,4-butanediol, 75.82 parts of diphenylmethane diisocyanate, 0.99 parts of ADR4468, and 0.4 parts of triethylenediamine; the preparation method is as follows:
[0045] The raw materials in the aforementioned parts by weight were mixed and added to a twin-screw reaction extruder at an extrusion temperature of 150° C. The extruded material was aged at 70° C. for 30 h to obtain a PPC-based high tensile strength TPU material having a molar ratio of soft segment to hard segment of 1:5.
[0046] Example 1
[0047] A PPC-based high-tensile strength TPU material is composed, by weight, of 100 parts of polypropylene carbonate, 13.07 parts of 1,4-butanediol, 48.89 parts of diphenylmethane diisocyanate, 0.81 parts of ADR4468, and 0.26 parts of triethylenediamine; the preparation method is as follows:
[0048] The raw materials in the aforementioned parts by weight were mixed and added to a twin-screw reaction extruder at an extrusion temperature of 180° C. The extruded material was aged at 80° C. for 24 hours to obtain a PPC-based high tensile strength TPU material having a molar ratio of soft segment to hard segment of 1:3.
[0049] Example 2
[0050] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is epoxidized soybean oil.
[0051] Example 3
[0052] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is ADR4368.
[0053] Example 4
[0054] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is ADR4380.
[0055] Example 5
[0056] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is ADR4385.
[0057] Example 6
[0058] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is ADR4400.
[0059] Example 7
[0060] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is KL-E4300.
[0061] Example 8
[0062] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is KL-E4370.
[0063] Example 9
[0064] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is KL-E4370B.
[0065] Example 10
[0066] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is X-U993.
[0067] Example 11
[0068] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is SAG-008.
[0069] Example 12
[0070] A PPC-based high tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the epoxy compound in this example is BTCE-9019.
[0071] Example 13
[0072] A PPC-based high-tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the catalyst in this example is N,N-dimethylcyclohexylamine.
[0073] Example 14
[0074] A PPC-based high-tensile strength TPU material, whose component ratio and preparation method are consistent with those of Example 1, except that the catalyst of this example is a mixture of triethylenediamine and stannous octoate.
[0075] Example 15
[0076] A PPC-based high-tensile-strength TPU material is composed, by weight, of 100 parts of polypropylene carbonate, 18 parts of 1,4-butanediol, 63 parts of diphenylmethane diisocyanate, 0.9 parts of ADR4468, and 0.33 parts of triethylenediamine. The preparation method is as follows:
[0077] The raw materials in the aforementioned parts by weight were mixed and added to a twin-screw reaction extruder at an extrusion temperature of 190° C. The extruded material was aged at 85° C. for 22 hours to obtain a PPC-based high tensile strength TPU material having a molar ratio of soft segment to hard segment of 1:4.
[0078] The TPU materials prepared in the above comparative examples and examples were respectively tested for hardness, tensile strength, elongation at break, and abrasion using GB / T531.1-2008 "Test method for indentation hardness of vulcanized or thermoplastic rubber - Part 1: Shore hardness method (Shore hardness)", GB / T1040.1-2018 "Determination of tensile properties of plastics", and GB / T9867-2008 "Determination of wear resistance of vulcanized or thermoplastic rubber (rotating roller abrader method)". The results are shown in the following table:
[0079]
[0080] As can be seen from the results in the table above, the comparative example and Example 1 have the same other parameters, but Example 1, when only the epoxy compound ADR4468 is added, achieves a significant improvement in tensile strength. This indicates that the addition of epoxy compounds is beneficial for improving the mechanical properties of PPC-TPU materials, especially significantly increasing their tensile strength to meet the application requirements of different scenarios. A comparison of the data from Examples 1-12 shows that the tensile strength of PPC-TPU materials increases differently after adding different epoxy compounds, demonstrating that different epoxy compounds improve the tensile strength of PPC-TPU materials to varying degrees.
[0081] At the same time, from the comparison between Comparative Example 2 and the embodiment of the present invention, it can be seen that when the ratio of the soft and hard segments in Comparative Example 2 changes, the tensile strength of the PPC-TPU material will also change, indicating that a reasonable ratio of the soft and hard segments is also important; however, as shown in Comparative Example 3, when the tensile strength is too high, the elongation at break is severely reduced, which also affects the application of the PPC-TPU material and is therefore not suitable for use.
[0082] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the scope of protection of the present invention.
Claims
1. A PPC-based high tensile strength TPU material, characterized by: The invention is composed of polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst.
2. The PPC-based high tensile strength TPU material according to claim 1, characterized in that: The mixing mass ratio of the polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst is 100:13.07-18:48.89-63:0.81-0.9:0.26-0.
33.
3. The PPC-based high tensile strength TPU material according to claim 2, characterized in that: The mixing mass ratio of the polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst is 100:14-16:52-58:0.85-0.88:0.29-0.
31.
4. The PPC-based high tensile strength TPU material according to claim 3, characterized in that: The mixing mass ratio of the polypropylene carbonate, 1,4-butanediol, diphenylmethane diisocyanate, epoxy compound and catalyst is 100:15:55:0.86:0.
3.
5. The PPC-based high tensile strength TPU material according to any one of claims 1 to 4, characterized in that: The epoxy compound is one of epoxidized soybean oil, ADR4468, ADR4368, ADR4380, ADR4385, ADR4400, KL-E4300, KL-E4370, KL-E4370B, X-U993, SAG-008 or BTCE-9019.
6. The PPC-based high tensile strength TPU material according to any one of claims 1 to 4, characterized in that: The catalyst is a tertiary amine catalyst, or a mixture of a tertiary amine catalyst and an organic tin catalyst.
7. The PPC-based high tensile strength TPU material according to claim 6, characterized in that: The tertiary amine catalyst is triethylenediamine or N,N-dimethylcyclohexylamine; the organic tin catalyst is one of stannous octoate, dibutyltin dilaurate or dibutyloctyltin dilaurate.
8. A method for preparing the PPC-based high tensile strength TPU material according to any one of claims 1 to 7, characterized in that: The components are mixed and then extruded using a twin-screw reaction extruder.
9. The method for preparing a PPC-based high tensile strength TPU material according to claim 8, wherein: The temperature of the twin-screw reaction extruder is 140-200°C.
10. The method for preparing a PPC-based high tensile strength TPU material according to claim 8, wherein: The TPU material extruded by the twin-screw reaction extruder needs to be matured at 70-90° C. for 20-30 hours.
Citation Information
Patent Citations
Preparation of thermoplastic polyurethane elastomer with polypropylene carbonate as soft segment
CN102838717A
TPU (thermoplastic polyurethane) hot melt adhesive film and preparation method thereof
CN117229746A